2015
DOI: 10.1016/j.jmoldx.2014.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Copy Number Alterations in Targeted, Amplicon-Based Next-Generation Sequencing Data

Abstract: Changes in gene copy number are important in the setting of precision medicine. Recent studies have established that copy number alterations (CNAs) can be detected in sequencing libraries prepared by hybridization-capture, but there has been comparatively little attention given to CNA assessment in amplicon-based libraries prepared by PCR. In this study, we developed an algorithm for detecting CNAs in amplicon-based sequencing data. CNAs determined from the algorithm mirrored those from a hybridization-capture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
113
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 118 publications
(116 citation statements)
references
References 20 publications
3
113
0
Order By: Relevance
“…1B); however, the CNA estimation confidence score (IQR value) was improved when using pooled germline samples (paired t test P ¼ 0.05). This was in line with other reports (14) that indicated that using pooled germline sequencing data as reference offered a robust method to identify gene CNAs.…”
Section: Cna Estimation Reproducibilitysupporting
confidence: 91%
See 1 more Smart Citation
“…1B); however, the CNA estimation confidence score (IQR value) was improved when using pooled germline samples (paired t test P ¼ 0.05). This was in line with other reports (14) that indicated that using pooled germline sequencing data as reference offered a robust method to identify gene CNAs.…”
Section: Cna Estimation Reproducibilitysupporting
confidence: 91%
“…Accurately assessing the depth of coverage of genes can be biased by high GC content and repetitive regions (11,14), so we first evaluated CNA reproducibility on a per-gene basis between technical replicates. Thirteen samples were sequenced in duplicate to assess technical variation; 12 of these duplicate datasets included repeated library preparation from the same DNA extraction, while one involved resequencing of the same library twice.…”
Section: Cna Estimation Reproducibilitymentioning
confidence: 99%
“…These findings are consistent with those reported by other investigators who have also recently demonstrated reliable detection of focal CNV loss or gain with the use of amplification-based sequencing data. 27,28 For annotation, we elected to limit the classification of variants as either pathogenic or variant of unknown significance. We used a strategy of treating oncogenes and tumor suppressor genes in two different ways in assigning pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…the difference in the number of forward vs. reverse reads containing the variant allele) >5-fold were removed from the variant set, as previously described 18 . Copy number alterations were identified clinically relevant at >|2| copies, as previously described 18,20 , using normalized, GC content corrected, total read counts per amplicon from each sample divided by those from a composite “normal” sample consisting of multiple single and pooled normal male DNA samples. Gene-level (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Gene-level (e.g. HER2 ) copy number estimates were determined by taking the coverage-weighted mean of the per-probe ratios, with expected error determined by the probe-to-probe variance, as previously described 20 .…”
Section: Methodsmentioning
confidence: 99%